Additive and Antagonistic Effects Among Combination of Agonists of Peroxisome Proliferator-Activated Receptor gamma (PPARg) on Transcriptional Activity - Daisuke Tsuriya; Hiroshi Morita; Tetsu Morioka; Shigekazu Sasaki; Yutaka Oki (Diabetes Research, 2015)
Objective: The Angiotensin-II receptor blocker telmisartan and sulfonylurea glimepiride may have clinical usefulness as partial agonists of PPARg. We investigated additive and antagonistic effects among combinations of telmisartan, glimepiride, and the Thiazolidinedione (TZD) selective PPARg agonist pioglitazone on transcriptional activity of PPARg. Materials/Methods: The receptors of pCMX-PPARg and pCMX-RXR, and PPRE-Luc reporter gene were transfected into CV1 cells, and treated with following agents, and luciferace assay was performed. Moreover, mammalian two-hybrid assay was done using GAL4 responsive reporter tk-MH100(UAS)×4-Luc and the chimeric receptor GAL4-PPARg. Results: Telmisartan increased transactivation of PPARg dose dependently. Activation by telmisartan 10 μM was 58.8% of that by pioglitazone 10 μM. Glimepiride also increased transactivation of PPARg dose dependently. Activation by glimepiride 10 μM was 49.8% of that by pioglitazone 10 μM. Addition of telmisartan 5 μM significantly enhanced transactivation by glimepiride 10 and 50 μM. Moreover, addition of pioglitazone 0.5 μM significantly enhanced transactivation by glimepiride 10 and 50 μM. Mammalian two-hybrid assay showed additive effect between glimepiride and telmisartan on binding of SRC-1 to PPARg. On the other hand, addition of glimepiride 10 and 50 μM reduced transactivation by pioglitazone 5 μM to 74% and 70%, respectively. Conclusion: Partial agonists of PPARg additively enhanced transactivation by other agonists, whereas high concentration of partial agonists reduced transactivation by full agonist antagonistically.